Perbaikan Laju Peningkatan Kuat Tekan Beton dengan Air IPAL Industri Beton Siap Pakai Menggunakan Accelerator - Prasetya Adi; Arusmalem Ginting; Elin Widiastuti; Dewi Listyowati (Universitas Sarjanawiyata Tamansiswa, 2026)
The concrete industry is one of the industries that uses large volumes of water. Water is used for the cement reaction process and for cleaning equipment. Wastewater treatment plants (WWTPs) are used to restore water quality before being released into the environment. This study was conducted to determine the suitability of treated wastewater for reuse in concrete production. Using WWTP water as a cement reagent is important for conserving groundwater and supporting the sustainability of the ready-mix concrete industry. Previous research has shown that the disadvantage of using treated wastewater in ready-mix concrete is low initial compressive strength. A practical way to increase initial compressive strength is to use an accelerator. Research is needed to increase initial compressive strength for several concrete grades. The use of water as a cement reagent requires certain quality standards, and the higher the planned concrete quality, the better the water quality required, approaching or equivalent to potable water. The study was conducted on two concrete grades to determine the effect of using wastewater treatment for ready-mix concrete on the properties of the resulting concrete. The concrete's compressive strength was tested using a standard test, using a cylinder with a diameter of 150 mm and a height of 300 mm, and workability was tested using an Abrahms cone. Previous research has shown that the use of treated wastewater affects the speed of the concrete hardening process. Therefore, in this study, an accelerator, an additive, was used to accelerate the cement reaction. The results of the study showed that the accelerator added material increased the quality of 20 MPa concrete by 114.452%, 112.091%, 105.671%, and 103.351% compared to concrete with normal water and increased the quality of 25 MPa concrete by 103.909%, 103.442%, 105.940%, and 108.756% compared to concrete with normal water. The rate of increase in the compressive strength of concrete with wastewater without accelerator and using accelerator can meet the requirements.